2017
DOI: 10.1038/s41467-017-01397-4
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature spontaneous superradiance from single diamond nanocrystals

Abstract: Superradiance (SR) is a cooperative phenomenon which occurs when an ensemble of quantum emitters couples collectively to a mode of the electromagnetic field as a single, massive dipole that radiates photons at an enhanced rate. Previous studies on solid-state systems either reported SR from sizeable crystals with at least one spatial dimension much larger than the wavelength of the light and/or only close to liquid-helium temperatures. Here, we report the observation of room-temperature superradiance from sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
126
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 39 publications
2
126
0
Order By: Relevance
“…An increase of the decay rate, or superradiance, was independently confirmed in our high-NV-density nanodiamonds through a set of scattering experiments 26 . Due to the large variation in ZPL position in a single nanodiamond, only sub-domains of NVs within narrow frequency windows are expected to act cooperatively.…”
mentioning
confidence: 98%
“…An increase of the decay rate, or superradiance, was independently confirmed in our high-NV-density nanodiamonds through a set of scattering experiments 26 . Due to the large variation in ZPL position in a single nanodiamond, only sub-domains of NVs within narrow frequency windows are expected to act cooperatively.…”
mentioning
confidence: 98%
“…We conclude with some remarks relating our findings to the recent studies of dipole force on colour centres embedded in nano-diamonds [13,14]. In the experiment [13], the underlying mechanism for the large dephasing at room temperature is mediated via phonon interactions [36] and consequently changes rapidly with the temperature of the lattice.…”
mentioning
confidence: 82%
“…In the experiment [13], the underlying mechanism for the large dephasing at room temperature is mediated via phonon interactions [36] and consequently changes rapidly with the temperature of the lattice. Since we have demonstrated that the presence of large collective dephasing is crucial to the observation of the enhanced dipole force, this raises the prospect of repeating the experiment [13], or even life-time measurements in [14], at lower temperatures. At lower temperatures, the dephasing will be reduced which should lead to a strong modification or even suppression of collective effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…where the summation is on the upper states for all allowed transitions between a state jñ | and the next state j 1 -ñ | down the SR cascade, with γ j,j−1 the corresponding transition rate [5]. In equation (19) we also assumed that all transitions result in the emission of a photon of energy ÿω. Although, as we will soon show, this is not the case for the interacting SR system, this approximation is perfectly adequate for the present discussion.…”
Section: Intensities and Timescalesmentioning
confidence: 99%